Characteristics of doripenem: a new broad-spectrum antibiotic - Francisco Alvarez-Lerma; Santiago Grau; Olivia Ferrández (Dove Medical Press, 2009)
Francisco Alvarez-Lerma1, Santiago Grau2, Olivia Ferrández21Intensive Care Unit, 2Pharmacy Department, Hospital Del Mar, Barcelona, SpainAbstract: Doripenem (S-4661) is a new parenteral antibiotic from the carbapenem class; similarly to imipenem and meropenem, it has a broad-spectrum activity against Gram-positive, Gram-negative, and anaerobic bacteria. It is active against multiresistant Gram-negative bacilli such as extended-spectrum beta-lactamase-producing (ESBL) Gram-negative Enterobacteriaceae and nonfermentative Gram-negative bacilli including some strains of Pseudomonas aeruginosa that are resistant to other carbapenems. Doripenem’s chemical structure is similar to that of meropenem (substitution of one sulfamoxil-aminomethyl chain for the dimethyl-carboxyl chain), and has one 1-beta-methyl chain which provides resistance to dehydropeptidase-I enzyme. The clinical trials conducted so far have focused on the treatment of severe infections such as complicated intra-abdominal infections, complicated urinary tract infections and pyelonephritis, nosocomial pneumonia, and ventilator-associated pneumonia. Given its activity profile and the results from the clinical trials, this antibiotic may be used for empirical treatment of multibacterial infections produced by potentially multiresistant Gram-negative bacilli. In 2007, the US Food and Drug Administration approved the use of doripenem for the treatment of complicated intra-abdominal infections and complicated urinary tract infections. The European Medicines Agency has approved the use of doripenem for the same indications in addition to nosocomial pneumonia regardless of whether it is ventilator-associated or not.Keywords: doripenem, antimicrobial activity, clinical efficacy, pharmacokinetics, tolerability